Characterization of manganese oxidation by Brevibacillus at different ecological conditions. (August 2018) - Zhao, Xin; Wang, Xiuheng; Liu, Bingfeng; Xie, Guojun; Xing, Defeng
Abstract: Bacterial Mn(II) oxidation plays an important role in the biogeochemical cycling of manganese and many trace metals. This study describes Mn(II) oxidation by two isolated manganese (Mn)-oxidizing strains that were identified and assigned as Brevibacillus brevis MO1 and Brevibacillus parabrevis MO2 based on physiochemical and phylogenetic characterizations. The ecological conditions influenced Mn(II) oxidation by both strains. Mn(II) stimulated the growth of strain MO2 while slightly inhibiting strain MO1. Mn(II)-oxidizing activity of two strains was enhanced with increase of initial pH, and maximum Mn(II)-oxidizing activity occurred at pH 8 for both strains (93.5%–94.0%). Brevibacillus showed the capability of mesophilic and psychrophilic Mn(II) oxidation. X-ray photoelectron spectroscopy (XPS) analysis indicated that the biogenic manganese oxides had an intermediate valence between 3 and 4. These results demonstrated that Brevibacillus, which is capable of oxidizing dissolved Mn(II), will be a suitable strain for exploring the mechanism of manganese oxidation in engineered and natural environments. Graphical abstract: Image 1 Highlights: Two species of Brevibacillus have the capability of manganese oxidation. Brevibacillus can oxidize 1 mM concentration of Mn(II). Brevibacillus has capability of manganese oxidation at low temperature (4 °C).